Isolation and molecular detection of avian mycoplasmosis in selected areas of Mymensingh district in Bangladesh (Asian Journal of Medical and Biological Research, 2021)
Avian mycoplasmosis caused by several species of Mycoplasma including Mycoplasma gallisepticum, M synoviae, M. meleagridis and M. iowae. Among these Mycoplasma gallisepticum is the most important poultry pathogen in Bangladesh. For effective control of Mycoplasmosis, proper early diagnosis is the corner stone. The research work was designed, a total of 20 samples, lung exudates, swabs from trachea and air sacs were collected from dead birds of different poultry farms in Mymensingh district during October-December, 2007. Samples were collected in 10% buffered formalin for histopathological study. Swabs were collected in mycoplasma broth supplemented with supplement-G. Additionally Kanamycin solution was added to prevent the growth of gram–Ve bacteria and then the organisms were transferred into mycoplasma agar for isolation. Histopathological studies were conducted using routine procedure in Hematoxylin and Eosin stain. Isolated Mycoplasma were subjected to DNA extraction, Nested PCR was done using a commercial PCR kit. The histopathological study revealed the presence of mycoplasmal related tissue changes, such as severe congestion and infiltration of mononuclear cells in different organs. The extracted DNA accumulated at the upper position of DNA ladder as band without any smear formation. The DNA from avian mycoplasmas was amplified and gave amplified product of 975 bp by outer primer and 395 bp by inner primer which was much smaller than the expected size. In this study, preliminary results from field samples suggest that culture using mycoplasma agar and broth supplement with Supplement-G and Kanamycin solution could be useful for the isolation of pathogenic avian mycoplasmas.Asian J. Med. Biol. Res. 2021, 7 (2), 182-190